Palladium-Catalyzed Asymmetric Allylic Alkylation of Azlactones: An Efficient Access to Unsaturated Trifluoromethylated α-Amino Acid Derivatives Possessing α-Quaternary Stereogenic Centers - Zhang, Shuaibo; Sun, Luyang; Li, Dong; Zhao, Jinfeng; Qu, Jingping; Zhou, Yuhan (Synthesis, 2024)
A new strategy for the asymmetric allylic alkylation of azlactones with α-(trifluoromethyl)allyl acetates catalyzed by Pd(OAc)2/(R)-BINAP is designed and developed, providing access to unsaturated α-quaternary α-amino acid derivatives bearing a trifluoromethyl group and contiguous quaternary and tertiary stereogenic centers. The products are obtained in good yields with exclusive regioselectivity and excellent stereoselective control under relatively mild reaction conditions. A scale-up experiment shows no loss of reactivity or stereoselectivity. The synthetic utility of the current strategy is demonstrated through transformations of a representative product to afford several potentially bioactive species.
Keywords: palladium catalysis; trifluoromethyl alkylation; asymmetric catalysis; azlactones; α-(trifluoromethyl)allyl acetates